Studi Kelimpahan Juvenil Ikan Pada Ekosistem Padang Lamun Di Perairan Karimunjawa, Kabupaten Jepara - Wizurai, Praressha; Redjeki, Sri; Hartati, Sri Turni (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Seagrass ecosystem of high organic productivity, with a high diversity of biota. On these ecosystems, diverse marine life such as fish juvenile, crustaceans, mollusks (Pinna sp, Lambis sp, Strombus sp), echinoderms (Holothuria sp, sp Synapta, Diadema sp, Arcbaster sp, Linckia sp) and worms (Polichaeta) (Bengen, 2001). The research was conducted at 10 stations. Sampling was conducted two times each observation station parallel to the shoreline and perpendicular to the shoreline using a small beam trawl. The results showed that the juvenile was found 27 species from 14 family. abundance average - average is 0.484 ind/m2 juvenile fish and the highest abundance at station 9 with the abundance of juvenile fish reaching ind/m2 1.40 and the lowest abundance found at station 3 and station 10 to the abundance of only 0.04 ind/m2 . The pattern of distribution of juvenile fish species tend to be random this is because in each station has similar characteristics.